Precursor models construction at preschool education: an approach to improve scientific education in the classroom - SABRINA PATRICIA CANEDO- IBARRA; JOSEP CASTELLO-ESCANDELL; PALOMA GARCIA-WEHRLE; ALEJANDRO RAFAEL MORALES-BLAKE (Metaichmio Publications, 2010)
This study aimed to explore young children scientific precursor models construction and how the designed teaching strategy was successful for improving science learning at preschool in a social context. We describe how 6 years old children built a precursor model of flotation based on density. The exploratory study used a qualitative data collection and analysis following a pre-interview, instructional process and post-interview design. On analyzing children's answers after the instructional period, we realized that several children were led to both the construction of a precursor model and a general qualitative upgrade in reasoning. We conclude that learning activities were effective and that the approach used in this study may help expand and improve teaching and learning of scientific concepts in preschool education